COVID-19 vaccine challenges: What have we learned so far and what remains to be done? - Forman, Rebecca; Shah, Soleil; Jeurissen, Patrick; Jit, Mark; Mossialos, Elias (Health policy (Amsterdam), 2021)
•Significant global interest exists around generation of safe and effective COVID-19 vaccines.•Addressing eleven challenges (among many others) could greatly benefit COVID-19 vaccine policies.•These challenges fall under three dimensions – vaccine development, dissemination, and deployment.•Decision-makers can anticipate and recognize these challenges, and strategize solutions at scale.•Effective vaccines can add to our existing arsenal of weapons against COVID-19. Developing and distributing a safe and effective SARS-CoV-2 (COVID-19) vaccine has garnered immense global interest. Less than a year after COVID-19 was declared a pandemic, several vaccine candidates had received emergency use authorization across a range of countries. Despite this scientific breakthrough, the journey from vaccine discovery to global herd immunity against COVID-19 continues to present significant policy challenges that require a collaborative, global response. We offer a framework for understanding remaining and new policy challenges for successful global vaccine campaigns against COVID-19 as well as potential solutions to address them. Decision-makers must be aware of these challenges and strategize solutions that can be implemented at scale. These include challenges around maintaining R&D incentives, running clinical trials, authorizations, post-market surveillance, manufacturing and supply, global dissemination, allocation, uptake, and clinical system adaption. Alongside these challenges, financial and ethical concerns must also be addressed.